2023
DOI: 10.13164/re.2023.0001
|View full text |Cite
|
Sign up to set email alerts
|

Performance on Cognitive Broadcasting Networks Employing Fountain Codes and Maximal Ratio Transmission

Abstract: The comprehensive performance of cognitive broadcasting networks employing Fountain codes (FC) and maximal ratio transmission (MRT) is investigated in the present paper. More precisely, the secondary transmitter (ST) employs Fountain code to effectively broadcast a common message such as a safety warning, security news, etc., to all secondary receivers (SRs) via underlay protocol of cognitive radio networks (CRNs). Different from works in the literature that are interested in studying the outage probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The Cumulative Distribution Function (CDF) [ 30 ] of server responses measured at two different places is shown in Figure 11 . From the perspective of system response, i.e., the time it takes for the measurement packet to travel from the device to the server and back, it can be observed that there were no fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…The Cumulative Distribution Function (CDF) [ 30 ] of server responses measured at two different places is shown in Figure 11 . From the perspective of system response, i.e., the time it takes for the measurement packet to travel from the device to the server and back, it can be observed that there were no fluctuations.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of the satellite-terrestrial networks, relaying networks, and Fountain codes-based networks were broadly addressed in [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. More precisely, Guo and other authors in [5] studied the performance of the two-way satellite-high altitude platform (HAP)terrestrial networks with non-orthogonal multiple access (NOMA).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the performance of the multi-hop with Fountain codes was given in [10] but the authors do not examine the satellite communications. The performance of the broadcast networks in cognitive radio networks (CRNs) with transmit and receive diversity techniques was examined in [11][12][13]. More precisely, they derived the cumulative distribution function (CDF), probability density function (PDF), and the average number of required time slots to broadcast a message to an arbitrary number of secondary receivers (SRs) in the closed-form expressions.…”
Section: Introductionmentioning
confidence: 99%